Konsep Pendekatan Saintifik di Sekolah Dasar - Silvia Lestari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In the implementation of the 2013 curriculum, the government has determined the scientific approach used in learning. So the teacher must understand the concept of the scientific approach. The aims of this research are 1) Explain the meaning of the scientific approach, 2) The steps of the scientific approach, and 3) The application of the scientific approach in elementary school. The results of this study are as a reference material for teachers to implement the scientific approach in the 2013 curriculum in schools.